Responses of macaque V1 neurons to binocular orientation differences. - Bridge, H; Cumming, BG (2001)
Interocular differences in orientation occur during binocular viewing of a surface slanted in depth. These orientation disparities could be exploited by the visual system to provide information about surface slant, but gradients of positional disparity provide an equally effective means to the same end. We examined the encoding of orientation disparities in V1 neurons that were recorded from two awake fixating monkeys. Monocular orientation selectivity was measured separately in each eye. Although the preferred monocular orientation in the left and right eyes was highly correlated (r = 0.98), 19 of 61 cells showed a significant interocular difference in preferred orientation (IDPO). By itself, an IDPO does not imply a specific binocular selectivity for orientation differences. We therefore examined the response to 25 binocular combinations of orientations by pairing each of five orientations in one eye with five in the other. Forty-four of 64 neurons showed responses that reflected the monocular orientation tuning selectivity; the preferred orientation disparity changed when the monocular orientation was changed in either eye. The remaining third (20 of 64) responded to a consistent orientation disparity in a way that was not simply predictable from monocular orientation selectivity. However, nearly all of these neurons were selective for positional disparity, and several characteristics of the responses suggest that the apparent selectivity for orientation disparities was just a consequence of the positional disparity sensitivity. Neither the data presented here nor previous data from the cat (Blakemore et al., 1972; Nelson et al., 1977) support the idea that a population of neurons early in the visual system has a separate encoding scheme for orientation disparities.